(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In machine age, peoplewere ancillary and things were central but in information age, things areancillary and knowledge is central. A company’s value derives not from thingsbut from knowledge, know-how, intellectual assets, and competencies – allembedded in people. Change, complexity and competition are buzzwords in today’sbusiness environment. A turbulent business environment, highly demandingcustomers, formidable competitors, technological innovations, shorteningproduct life cycles and low barriers to entry, have forced organizations to puta higher emphasis on learning. Organizations are becoming more fluid,facilitating networks of customers, suppliers and business partners. Boundariesof organizations are becoming blurred and departmental barriers are fading.